The relationship between parenting stress and preschool children’s social–emotional competence: the chain mediating role of parental reflective functioning and parent–child relationship - Yu, Sisi; Liao, Mingying; Liu, Xinyi; Li, Yanyan (Frontiers in Psychology, 2025)
IntroductionGiven the significance of social-emotional competence for the success and well-being of preschool children and the crucial role of the family environment in children’s upbringing, the purpose of this study is to explore the effect of parenting stress on preschool children’s social-emotional competence, and to examine the mediating roles of parental reflective functioning and the parent-child relationship through a chain mediation model.MethodsA total of 3,166 parents of preschool children aged 3-6 years in China were surveyed using the Parenting Stress Index Short Form, the Chinese Inventory of Children’s Socioemotional Competence, the Child-Parent Relationship Scale, and the Parental Reflective Functioning Questionnaire.ResultsThe results showed two main findings: (a) parenting stress, parental reflective functioning, the parent-child relationship, and preschool children’s social-emotional competence were significantly correlated, and parenting stress negatively predicted preschool children’s social-emotional competence; and (b) parental reflective functioning and the parent-child relationship played significant mediating roles between parenting stress and preschool children’s social-emotional competence. The analysis revealed three mediating pathways: (a) the separate mediating role of parental reflective functioning; (b) the separate mediating role of the parent-child relationship; and (c) the chain mediating role of parental reflective functioning and the parent-child relationship.DiscussionThis study contributes to research in the field of social-emotional competence and provides a theoretical basis for improving preschool children’s social-emotional competence.